Environmental Education for High School and Vocational School of Muhammadiyah City of Medan Based On Islam - Efendi Agus; Khaidir Ali (Budapest International Research and Critics University, 2022)
High School Educational Institutions (SMA) and Vocational High Schools (SMK) should have the concept of introducing, maintaining and preserving ecological and environmental sustainability which is integrated in the curriculum applied in SMA and SMK Muhammadiyah Medan City. Environmental education so far still needs to be implemented in the model of education in schools, although in the school curriculum there are already learning objectives that contain about the environment. The results of initial observations in SMA, SMK Muhammadiyah are still many infind discrepancies between the provisions of environmental education policies and the appearance of the environmental situation contained in the SMA, SMK Muhammadiyah North Sumatra in general and the city of Medan in particular. So this study only examines in terms of: Availability of Environmental Education policies from aspects, Provision of clean water, waste water management, school waste management, and a Green school environment. The process of this research is to make observations related to the availability of Environmental Education policies and conduct an assessment and analysis of the data obtained related to the aspects studied. The results of this study are used as information material to explain the success that has been achieved bySMA, SMK Muhammadiyah related to the availability of Environmental Education policies from these aspects. At the same time, it is hoped that it can be used as reference material by decision makers in this case the relevant leaders in formulating appropriate environmental education provisions/policies.